The Revised Standard Version (1952) and its revisions as a linear emergence of the Tyndale–King James Version tradition - Cynthia L. Miller-Naudé; Jacobus A. Naudé (HTS Teologiese Studies/Theological Studies, 2022)
Revisions of the King James Version of 1611 continued into the 20th and 21st centuries as literal or word-for-word translations. This development corresponds with a new age in Bible translation that started in the second half of the 20th century, which involves at least six changes in the philosophy of Bible translation. Firstly, Bible translation is characterised by interconfessional cooperation. Secondly, the plain meaning intended in the incipient texts is made accessible to readers. Thirdly, new critical editions of the Hebrew and Greek incipient texts on the basis of new discoveries of texts are utilised. Fourthly, there is the tendency to remove archaic language to make versions intelligible. Fifthly, there is a tendency to use gendered and inclusive language. Sixthly, the move is from print communication, which can be typified as typographic interpretive culture, to electronic or media communication, which can be typified as digital-media interpretive culture, where sound and visuality become prominent as a contextual supplement to words. In the analysis it will be determined which of these aspects are reflected in the Revised Standard Version and its revisions as part of the linear emergence of the Tyndale–King James Version tradition. However, unlike the King James Version, the Revised Standard Version and its revisions failed to achieve widespread approval from satisfied readers, thus opening the door to alternative revisions.